Body Mass Index Status of First Year Medical Students - Rahman, Md Azizur; Begum, Jebunnessa; Wahab, Md Abdu (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Body mass index (BMI) is an important tool for indirect measure of nutritional status of an individual. Overweight and obesity are recognized as “escalating epidemics” affecting both developed and developing countries. An obese (BMI ≥30 kg/m2) individual is more likely to get hypertension, heart disease, diabetes mellitus, cardiovascular disease, gall bladder disease and various types of cancer. Aim: To assess the prevalence of overweight and obesity among students of Armed Forces Medical College (AFMC) and factors associated with obesity. Methods: A descriptive cross-sectional survey was conducted in the Department of Anatomy among 101 students ‘AFMC Medical cadets’ category from November 2019 to January 2020. Data were collected using pretested questionnaire after taking verbal consent from the participants and administrative authority. The height and weight of the cadets were measured and the BMI was calculated. Results: Among the 101 Medical cadets of Armed Forces Medical College, the mean ± SD height of the students was 1.6.±0.08 m, while the mean weight was 63.6±12.1 kg and the mean BMI 24.0±4.3 kg/m2. Normal BMI was observed in 65.6% students, while 24.2% students were overweight, 10.1% obese and only 2.2% underweight. Overweight and obesity were significantly more in male than female students. Conclusion: The present study gives an idea about the alarming prevalence of overweight and obesity among the ‘AFMC Medical Cadets’ category. There is a need to create awareness and interest regarding healthy diet and body weight management among this future physician population. Nutritional education on dietary practices and life style change should be built in as supporting educational activity during each calendar year. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 16-18